Empowerment of Marketing Strategies of Angkringan Traders Through Social Media During Covid-19 Time in Ponorogo - Amar Alam Al Firdaus; Evi Muafiah; Muhammad Heriyudanta; Israa Al_Barazanchie (Jurnal Pengabdian dan Pemberdayaan Masyarakat Indonesia, 2021)
The 2021 KPM-DDR activity will be held in Jingglong Village, Ponorogo District, Ponorogo Regency. We and the community chose the personal asset owned by Mrs. Siti Zulaecha, namely the Angkringan business, on the grounds that the development of personal assets is aimed at making the business owned by Mrs. Siti Zulaecha more developed, especially in this Covid-19 pandemic situation. In a pandemic situation like this, it has a big impact, one of which is in the economic sector, moreover the government has issued a letter related to PPKM policies, one of which is the implementation at 20.00 WIB. Therefore, angkringan businesses that are known to be open until 12 hours and above must be closed according to government policy. The marketing strategy that we did to develop the angkringan business was by making branding, posters and uploading on social media such as Instagram, Facebook and WhatsApp as well as financial management applications. KPM-DDR activities use the ABCD (Asset Based Community Development) method through four stages of implementation, namely inculturation, discovery, define, reflection and RTL. The result of this activity is to implement online marketing strategies through social media and the use of financial management applications can increase revenue and help angkringan business owners discipline financial bookkeeping. In addition, it makes angkringan businesses survive in the midst of a pandemic situation with new innovations to market them on social media.